2019
DOI: 10.1016/j.celrep.2019.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Blocking and Membrane-Proximal Domain Targeting Anti-OX40 Antibodies Mediate Potent T Cell-Stimulatory and Anti-Tumor Activity

Abstract: Highlights d Anti-OX40 mAbs do not require CRD1-binding and nonligand blocking for activity d A ligand-blocking CRD2-targeting mAb displays strong agonistic activities d A membrane-proximal CRD4-targeting mAb shows potent agonistic functions d Agonistic mAbs against different TNFRs need to be screened on an individual basis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…who also demonstrated strong agonistic function with a CRD4 binding anti-mOX40 mAb. However, those authors also documented equivalent agonistic activity with a CRD2-binding, ligand blocking anti-mOX40 mAb [23], indicating the fine epitope is also important, as we reported previously for anti-CD40 [22].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…who also demonstrated strong agonistic function with a CRD4 binding anti-mOX40 mAb. However, those authors also documented equivalent agonistic activity with a CRD2-binding, ligand blocking anti-mOX40 mAb [23], indicating the fine epitope is also important, as we reported previously for anti-CD40 [22].…”
Section: Discussionsupporting
confidence: 82%
“…Previous work studying the mechanisms of action of therapeutic antibodies has shown that the region of the molecule targeted is also an important consideration, with even subtle shifts in binding epitope resulting in large impacts on effector function and efficacy [19,20]. Recent work on several TNFRs has further highlighted the importance of these aspects in influencing the type and strength of effector function [20][21][22][23]. For example, we demonstrated the importance of domain binding on the biological activity of anti-CD40 mAb, showing that membrane distal CRD1binding mAb were strong agonists of CD40 with membrane proximal mAb less potent [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heterogeneity has often frustrated efforts to develop ligand mimics that can selectively activate one signaling pathway, as the molecular requirements for binding different complexes are often highly overlapping. Antibodies have been developed that can induce receptor dimerization, but the location of the epitope that the antibodies target generally does not lead to cross-linking of receptors in their native "activated" arrangement (1). Because the geometry of the dimerized receptor pair greatly influences their activity, a better strategy is needed to obtain functional antibodies.…”
mentioning
confidence: 99%
“…The author declares that he has no conflicts of interest with the contents of this article. 1 To whom correspondence should be addressed: Cancer Immunology Discovery Oncology R&D Group, Pfizer Inc., 10777 Science Center Dr., San Diego, CA 92121. E-mail: Dirk.Zajonc@pfizer.com.…”
mentioning
confidence: 99%